Fistula Repair After Hypospadias Surgery Using Buccal Mucosal Graft - Hosseini, Jalil; Kaviani, Ali; Mohammadhosseini, Mojtaba; Rezaei, Alireza; Rezaei, Iraj; Javanmard, Babak (Urology Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-language:FA; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Introduction: The aim of this study was to evaluate the success rate of urethrocutaneous fistula repair using buccal mucosal graft in patients with a previous hypospadias repair. Materials and Methods: We reviewed records of our patients with urethrocutaneous fistula developed after hypospadias repair in whom buccal mucosal graft fistula repair had been performed. All of the patients had been followed up for 24 postoperative months. A successful surgical operation was defined as no fistula recurrence or urethral stricture. Retrograde urethrography and urethrocystoscopy would be performed in patients who had any history of decreased force and caliber of urine or any difficulty in urination. Results: Fistula repair using buccal mucosa patch graft had been done in 14 children with urethrocutaneous fistula developing after hypospadias reconstruction. The mean age of the children was 8.70 Â± 1.99 years old (range, 4 to 11 years). Seven fistulas were in the midshaft, 4 were in the penoscrotal region, and 3 were in the coronal region. Repair of the fistulas was successful in 11 of 14 patients (78.6%). In the remaining children, the diameter of the fistula was smaller than that before the operation, offering a good opportunity for subsequent closure. <!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–>Conclusion: Our findings showed that fistula repair using buccal mucosal graft can be one of the acceptable techniques for repairing fistulas developed after hypospadias repair.